Teachers’ pedagogical mathematical awareness in diverse child-age-groups - Björklund, Camilla; Barendregt, Wolmet (NOMAD Nordic Studies in Mathematics Education, 2016)
In this study we investigate preschool teachers’ attention to number sense, number sequence, geometrical shapes and patterns, and their pedagogical awareness regarding these areas in their work with younger and older preschool children. The specific research questions are: Are there differences in teachers’ attention to the different mathematical content areas depending on the age group they are teaching? And if mathematical content areas show differences between age groups, what pedagogical awareness levels constitute these differences? The study shows that the frequency of working with mathematical content is higher for all areas regarding older children, but teachers’ choice of mathematical content area is not necessarily depending on the age of the children. Teachers’ frequency of observing and engaging children in mathematics is lower among those working with younger children but the difference is in general quite small. Significant and substantial differences appear in teachers’ attention to children’s mathematizing initiatives and problematizing number sequences, geometrical shapes and patterns.